The Effect of the Constitutional Court Decision Number: 46/PUU-VIII/2010 on the Inheritance Rights of Out-of-Wedlock Children in Islamic Inheritance Law - Dwi Anggriani Salsabila A A Sanmas; Novyta Uktolseja; Muchtar Anshary Hamid Labetubun (LUTUR Law Journal, 2025)
This article examines the issue of inheritance rights for out-of-wedlock children from the perspective of Islamic law and Indonesian national law, particularly in the aftermath of Constitutional Court Decision Number: 46/PUU-VIII/2010, which marked a shift in the recognition of the civil status of out-of-wedlock children in relation to their biological fathers. This article aims to analyze the impact of Constitutional Court Decision Number: 46/PUU-VIII/2010 on the legal inheritance status of out-of-wedlock children within the frameworks of Islamic law and Indonesia’s national legal system. This study employs a normative juridical method with a statutory and conceptual approach. Data sources include primary and secondary legal materials. The research findings indicate that the Constitutional Court decision grants civil legal recognition to out-of-wedlock children with regard to their biological fathers, provided that the relationship can be proven through scientific means or valid legal evidence. This ruling broadens the inheritance rights of out-of-wedlock children under national law. However, in Islamic legal tradition, lineage (nasab) remains the principal basis for inheritance, leading to a tension between sharia principles and state law. The decision also opens a discourse on the harmonization of Islamic law and national law in order to protect the rights of children.